Understanding the role of micro-organisms in the settlement of coral larvae through community ecology - Abigail C. Turnlund; Paul A. O’Brien; Laura Rix; Nicole Webster; Miguel Lurgi; Inka Vanwonterghem (Marine Biology, 2025)
Successful larval recruitment is essential to the growth of coral reefs and therefore plays a key role in the recovery of degraded reefs worldwide. The rising intensity and frequency of environmental disturbance events and their effect on the establishment of new corals is outpacing the natural capacity of coral reefs to recover. To counter this, restoration programmes are increasingly turning to interventionist approaches to enhance coral recruitment, including mass-breeding corals in aquaria for subsequent deployment in the field. Coral sexual propagation has the potential to generate large numbers of genetically diverse coral recruits, but widespread application is still limited by the ability to reliably guarantee the successful settlement of coral larvae. Identifying the origins of biochemical cues that enhance coral settlement is a prerequisite to improving coral larval settlement on key locations and substrates. Microbial biofilms and microbes associated with crustose coralline algae have been shown to induce coral larval settlement, yet the specific taxa and mechanisms involved are poorly understood. In this review we synthes current literature on microbial settlement cues and the challenges associated with untaizengling the origin of individual cues originating within complex microbial communities. Furthermore, we call attention to the importance of interrogating microbial interactions with a holistic community approach to further our knowledge of both coral larval settlement inducers and inhibitors. Obtaining a better understanding of microbial interactions associated with coral settlement will lead to more effective approaches to restoration, from engineering inductive microbial communities to synthesising biochemical cues that can support coral larval settlement for aquaculture and reef recovery.